Effect of feeding undegradable dietary protein on milk production of crossbred cows - SAMPATH, K T; PRASAD, C S; RAMACHANDRA, K S; SUNDARESHAN, K; RAO, A SUBBA (The Indian Journal of Animal Sciences, 2013)
Fourteen crossbred cows in 2 to 5 lactation, whose previous lactation yield was 8 to 10 kg/day were divided into 2 equal groups based on their body weight, previous lactation yield and lactation number. They were fed isocaloric concentrate mixtures containing 35% UDP in CP (group I) or 50% UDP in CP (group In from 15 day after calving up to 252 days. Ragistraw was the sole source of roughage for both the groups. The average yield of fat corrected milk/day/cow was significantly higher in group II (9.4 kg) when compared with group I (7.8 kg). With the progress of lactation, the magnitude of decline in milk yield was much lower in group II than group I. It was infered that providing higher amounts of bypass protein in the diet of lactating cows maintained on straw-based diet enhances milk production.